Increasing efficiency (Aircraft Engineering and Aerospace Technology, 1971)
It was found that the fluorocarbon resins in the hundred or so bearing bushes which support the variable geometry inlet guide vanes in the high pressure compressor of the Rolls Royce Spey gas turbine engine were subject to serious corrosion.